PENDEKATAN FILSAFAT ILMU DAN FENOMENA COPERNICUS - Huda, Atok Miftahul (Jurnal Bestari, 1992)
Nicolaus Copernicus often remembered as the leading Poland saint. Sometimes, men referred him as scientist and philosofer. As a great scientist, he once shocked the Church when he offering heliocentrism. This theory supported Galileo's idea and rejected Ptolemy's geocentrism. Every student can refer his scientific achievment and conclude philosophical foundations to widen the range of his research adventure. We can understand the origin and development of of epistemology from his philosopical ideas.